2015
DOI: 10.1128/jcm.01249-15
|View full text |Cite
|
Sign up to set email alerts
|

Human Wound Infection with Mannheimia glucosida following Lamb Bite

Abstract: e Mannheimia spp. are veterinary pathogens that can cause mastitis and pneumonia in domestic cattle and sheep. While Mannheimia glucosida can be found as normal flora in oral and respiratory mucosa in sheep, there have been no reported cases of human infection with this organism. CASE REPORTA 64-year-old man sustained a bite on the right thumb from a 10-month-old lamb. The lamb's teeth punctured his thumbnail while he was holding the lamb's mouth open during anthelminthic treatment with a malfunctioning dosing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…A recent study has reported alterations in semen parameters in experimental bucks challenged with M. haemolytica [ 26 ]. Despite the fact that this pathogen usually affects ruminants, it has been already identified in humans associated with different conditions [ 27 , 28 ], and it has been reported that infections in humans may occur, especially upon contact with colonized animals [ 29 ]. To the best of our knowledge, this genus has not been reported before in semen samples from humans with fertility issues.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has reported alterations in semen parameters in experimental bucks challenged with M. haemolytica [ 26 ]. Despite the fact that this pathogen usually affects ruminants, it has been already identified in humans associated with different conditions [ 27 , 28 ], and it has been reported that infections in humans may occur, especially upon contact with colonized animals [ 29 ]. To the best of our knowledge, this genus has not been reported before in semen samples from humans with fertility issues.…”
Section: Discussionmentioning
confidence: 99%
“…Two other Gammaproteobacteria, Mannheimia and Halomonas, were significant indicators. Mannheimia , formerly termed Pasteurella and believed to be veterinary pathogens, are implicated in human infections (Hadjadj et al., ; Lau et al., ). Halomonas, a potentially pathogenic halophile, is noted in African and Korean microbiomes, purportedly due to fermented dairy or fish consumption (Ogier et al., ; Park, Yi, Jeon & Kang, ; Pieretti et al., ; Seck et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Others are pathogenic, such as Mannheimia haemolytica , which is one of the most important respiratory pathogens of domestic ruminants and causes serious outbreaks of acute pneumonia in neonatal, weaned and growing lambs, calves and goats [5] . Infections are rare in humans but can be fatal when they do occur [6] , [7] .…”
Section: Introductionmentioning
confidence: 99%